[OP.5C.02] ASSESSING THE IMPACT OF BIRTH WEIGHT AND POSTNATAL WEIGHT GAIN ON OFFICE AND 24-HOURS AMBULATORY BLOOD PRESSURE IN CHILDREN AT FIVE AND TEN YEARS OF LIFE. (September 2017) - Álvarez, J.; Torro, I.; Aguilar, F.; Redon, P.; Redon, J.; Lurbe, E.
Abstract : Objective: To assess the impact of birth weight and postnatal weight gain on BP tracking at 5 and 10 years of life, in order to identify a window of opportunity for early intervention. Design and method: This prospective study, starting at birth, includes eighty-seven subjects born at term. Subjects were divided, according to size at birth, in small, appropriate and large for gestational age. Children were followed up at 5 and 10 years and anthropometric parameters and BP (office and 24-hours ABPM) were obtained. The BP tracking from birth to 5 and 10 years and the ratio to weight gain in each period were calculated. Results: Overall, weight gain during the first 5 years and thereafter between 5 and 10 years were 18.6 ± 5.3 kg and 20.9 ± 8.9 kg, respectively. Anthropometric parameters and systolic BP at birth, 5 and 10 years grouped by BW conditions are in the table. At birth significant differences in systolic BP were present among groups increasing as the BW increases. In the first 5 years, the steepest increment in systolic BP related to weight gain was present in SGA as compared to AGA and LGA. Differences in BP tracking among BW groups disappeared after the age of 5. Figure. No caption available. https://services.aimgroup.it/ASPClient/files/3465/Abstract/669_20170105101936.png Conclusions: This prospective study points out that the steepest BP tracking was during the first five years of life in those subjects that were born SGA independent of the postnatal weight gain. The recognition of critical periods, may contribute to open a window of opportunity to modify BP tracking in subjects with potential risk.